Locally adapted Brazilian ewes with different coat colors maintain homeothermy during the year in an equatorial semiarid environment - Leite, Jacinara Hody Gurgel Morais; Da Silva, Roberto Gomes [UNESP]; da Silva, Wallace Sostene Tavares; da Silva, Wilma Emanuela; Paiva, Renato Diógenes Macedo; Sousa, José Ernandes Rufino; Asensio, Luis Alberto Bermejo; Façanha, Débora Andrea Evangelista (Springer Nature, 2018)
The present paper aimed to show the thermoregulatory responses of locally adapted Morada Nova sheep with different coat colors that were exposed to direct solar radiation in an equatorial semiarid region. Animals were classified into four groups according to the coat color as follows: (1) dark red, (2) intermediate red, (3) light red, and (4) white coats. Forty Morada Nova ewes were observed in for 7 consecutive months. The experimental variables measured were rectal temperature (RT), skin surface temperature (ST), respiratory rate (RR), skin surface evaporation (CE), respiratory evaporation (RE), and heat exchange by convection (HC) and radiation (R). Data were collected from 1100 to 1400 h after the animals were exposed to 30 min direct sunlight. The results showed that all groups maintained homeothermy. The RR was higher in the animals of groups 1 to 3, which also showed higher values for ST when compared to the white-coated animals. Sensible heat exchange mechanisms were not important for heat loss, and R was a significant source of heat gain from the environment for the animals. Groups 1, 2, and 3 used RR more intensely than group 4 (P value = 0.001); however, CE was higher for the white-coated animals. It was concluded that Morada Nova sheep are well adapted to the semiarid environment, regardless of coat color.
Keywords: Adaptation; Cutaneous evaporation; Equatorial semiarid; Homeothermy; Naturalized breed; Thermoregulatory mechanisms